An Analysis on Learning Styles and Personality Types of Students in the Techniques of Architectural Presentation Course - Berkan, Saliha Türkmenoğlu; Öztaş, Saniye Karaman (My University, 2023)
Determining the learning styles of the students in the process of constructing curricula is significant for the development of architectural education. This study aimed to evaluate the relationship between the learning style of first-year architecture students and their successful performance in \"The Techniques of Architectural Presentation\" course and to discuss the relationship between learning styles-gender and learning styles-course curriculum. Kolb and Briggs Myers learning style inventories were used in the study. It was determined that the students with a diverging style had a large share of participants, and no significant relationship was established between gender, course success, and Kolb’s learning style. According to the MBTI inventory, it was determined that the differences in the mean scores of the students' genders in the \"Intuition\", \"Feeling,\" and \"Perception\" profiles were significant. An increase in success rate in 3D studies indicates the importance of the development of syllabi with 3D applications.
Keywords: Personality types; Learning styles; Architecture education; Kolb; Briggs Myers